Study the orientation and distance factors effects on the lower usable frequency ((LUF)) over middle east region - Hadi, Khalid A. (Iraqi Journal of Physics, 2012)
In this research, the influence of the orientation and distance factors on the lowest usable frequency (LUF) parameter has been studied theoretically. The calculations of the (LUF) parameter have been made using the (VOACAP) international communication model for the connection links between the capital Baghdad and many other locations that distributed on different distances and directions over the Middle East region. The results shown in this study indicate there is a slight affection of the link direction (orientation) on the LUF parameter, while the influence of the distance factor is more significant on the values of the LUF parameter. The day/night effect appears for the long distance HF links (i.e. more than a 500 Km)